Screening and optimisation study on antioxidant extracts from selected lamiaceae plants - Mohd Shaiful Azman, Abdul Rahim (2010)
This thesis deals with screening of antioxidant activity, phenols content and mineral profiles, optimisation of extraction of antioxidants and optimisation of spray drying of boiling extract from the selected Lamiaceae plants. The objective of this thesis was to select the plant materials of the selected Lamiaceae species that gave the highest antioxidant activity, highest phenols content and best mineral profiles. This thesis presents the optimised levels of experimental variables that gave the highest antioxidant activity-yield. This thesis also presents the optimum levels of the operational variables that influence the spray drying of the liquid extract of the Lamiaceae plant. Fresh Plecranthus amboinicus Lour. Indonesia (PALl) samples were randomly collected from Jakarta, Indonesia and samples of Plecranthus amboinicus Lour. Malaysia (PALM), Pogostemon cablin Benth. (PCB), SOlenostemon scutellariodes Benth. Red (SSR) and Solenostemon scutellariodes Mix Colour (SSMC) were randomly collected from Kuantan, Malaysia. The extracted samples were assessed using 1,1-diphenyl-2- picry1hydrazyl (DPPH) free radical scavengiig assay for determination of antioxidant activity. Folin Ciocalteau method was chosen for total phenols determination, while the essential minerals were analysed by using atomic absorption spectrometer. The 22 factorial design of experiment was used in the optimisation of extraction of antioxidants by boiling. The method of Path of Steepest Ascent was used to maximise the antioxidant activity in the spray dried extract. The obtained results indicated that the - leaves tissues of PCB samples exhibited the significant 6<0.05) highest antioxidant activity (63.18%) and highest phenols content (7.64 mg/g fresh weight) while the highest total minerals content was observed in the PALl leaves (38.41 ppm). For optimisation of extraction of antioxidant by boiling, the theOretical maximum point has the boiling temperature (T) at 116.18°C and boiling time duration (t) at 107.81 minutes which gave an antioxidant activity-yield of 65.153 ' %. The combination of levels of operational variables where the spray dryer was operated at X1 (temperature) = 177.65°C and X2 (concentration of maltodextrin) = 48.65% gave the highest yield of antioxidant activity of spray dried extract. This research suggests a chemical basis for some of the health benefits claimed for in folk medicine and warrant further studies to develop it as a natural functional food.